A Olimpíada Brasileira de Física no Estado de São Paulo e a difusão do conhecimento na Universidade de São Paulo (Revista de Cultura e Extensão USP, 2009)
Science competitions, such as the Brazilians Physic, Mathematical, Chemical, Astronomy and Biology Olympiads, are becoming popular and every year thousands of students from basic to high schools are attracted to participate motivated by the challenges. These competitions are becoming powerful criteria to evaluate the education system as well.Since 2006 the Instituto de Física de São Carlos is the institution that coordinates the Brazilian Physics Olympiad (OBF) at São Paulo state. Parallel with the regular calendar of the OBF, activities such as: visits, courses, seminars were happens and opened to all community. In this paper we analyze the results of these activities as a way to promote the knowledge dissemination produced in the University.